Determination of the Relative Potency of Norepinephrine and Phenylephrine Given as Infusions for Preventing Hypotension During Combined Spinal-Epidural Anesthesia for Cesarean Delivery: A Randomized Up-And-Down Sequential Allocation Study - Qian, Jing; Zhao, Yan-Ping; Deng, Jia-Li; Wang, Li-Zhong; Xiao, Fei; Shen, Bei; Yao, Han-Qing (Frontiers in Pharmacology, 2022)
Abstract Purpose: The relative potency of norepinephrine and phenylephrine given as boluses to treat hypotension during spinal anaesthesia for cesarean delivery has been reported but few data are available for infusions.This study aimed to determine the relative potency of norepinephrine and phenylephrine when given by infusion for preventing hypotension during combined spinal-epidural anaesthesia for cesarean delivery. Methods: This was a prospective, randomized, double-blind, up-and-down sequential allocation study. Patients were randomly allocated to receive a prophylactic infusion of norepinephrine or phenylephrine started immediately after induction of anaesthesia.The first patients received either norepinephrine 0.1 μg/kg/min or phenylephrine 0.5 μg/kg/min. An effective infusion rate was defined when no hypotension occurred before delivery. For each subsequent patient, the norepinephrine infusion rate was decreased or increased by 0.01 μg/kg/min or the phenylephrine infusion rate was decreased or increased by 0.05 μg/kg/min according to whether the infusion was effective or ineffective respectively in the previous patient. Values for the infusion rate that was effective in preventing hypotension in 50% of patients (ED50) for norepinephrine and phenylephrine were estimated using up-and-down sequential analysis and relative potency was estimated. Probit regression was used as a backup and sensitivity analysis. Results: The ED50 values for norepinephrine and phenylephrine calculated by the up-and-down method were 0.061 (95% CI 0.054 to 0.068) μg/kg/min and 0.368 (95% CI 0.343 to 0.393) μg/kg/min respectively. The estimated relative potency ratio for norepinephrine to phenylephrine was 6.03:1 (95% CI 5.26:1 to 6.98:1). Conclusions: Under the conditions of this study, norepinephrine given by infusion was 6 times more potent than phenylephrine. This imformation is useful for clinical practice and further comparative studies of norepinephrine versus phenylephrine.